2016
DOI: 10.1175/jpo-d-14-0201.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Consumption of Antarctic Bottom Water in the Abyssal Ocean

Abstract: Manuscript (non-LaTeX)Click here to download Manuscript (non-LaTeX) Full manuscript.docx ABSTRACT 24The abyssal ocean is primarily filled by cold, dense waters formed around Antarctica and 26 collectively referred to as Antarctic Bottom Water (AABW). At steady state, AABW must be consumed in the ocean interior at the same rate it is produced, but how and where this 28 consumption is achieved remains poorly understood. Here, we present estimates of abyssal water mass transformation by geothermal heating and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
149
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 127 publications
(169 citation statements)
references
References 102 publications
11
149
0
Order By: Relevance
“…This expression for the full diapycnal velocity, normal to the isopycnal, is derived, for example, in Marshall et al (1999) but differs from the one reported in McDougall (1984) andde Lavergne et al (2016), who only considered its vertical component. This difference is important when considering regions of weak vertical stratification like the turbulent BBLs.…”
Section: July 2016mentioning
confidence: 95%
See 4 more Smart Citations
“…This expression for the full diapycnal velocity, normal to the isopycnal, is derived, for example, in Marshall et al (1999) but differs from the one reported in McDougall (1984) andde Lavergne et al (2016), who only considered its vertical component. This difference is important when considering regions of weak vertical stratification like the turbulent BBLs.…”
Section: July 2016mentioning
confidence: 95%
“…Here, we will consider the simpler case of a linear equation of state, which is sufficient to study the qualitative aspects of mixing-driven flows. The reader is referred to the recent paper by de Lavergne et al (2016) for a discussion of the mass transport generated by mixing in the abyssal ocean with a nonlinear equation of state. Our goal is to illustrate how interior mixing drives both downwelling across density surfaces in the ocean interior and upwelling along the boundaries, rather than providing an accurate estimate of the observed ocean overturning circulation.…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations